HYDROCARBONS AND BACTERIAL ACTIVITY IN MANGROVE SEDIMENTS FROM GUANABARA BAY, BRAZIL - Wasserman, Julio César; Botelho, André Luiz Magalhães; Crapez, Mirian Araujo Carlos; Bispo, Maria das Graças Silveira; Silva, Frederico Sobrinho da; Filgueiras, Conceição Maria (Geochimica Brasiliensis, 2012)